(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2014)
Although the cause of anorexia nervosa (AN), a disease characterized by excessive food restriction and irrational fear of gaining weight, is still unknown, it is believed that its etiology is multifactorial, including genetic and psychological factors. Currently there is no effective treatments for the disease, and most patients drop out of treatment, or show a minimum improvement or relapse after it. Cognitive-behavioral therapy (CBT), which focuses on treatment adherence, weight gain and the development of a regular and flexible eating pattern, has been seen as a possible treatment for AN. Several cognitive-behavioral models have been proposed, developed and tested, but, their long-term effectiveness is not well established. The current study is a review of recent studies investigating the role of TCC in anorexia nervosa, aiming at an update of information regarding the effectiveness of cognitive-behavioral therapy in anorexia nervosa, with focus on nutritional treatment.